DETERMINAN KEBERHASILAN LELANG EKSEKUSI HAK TANGGUNGAN PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG JAKARTA I TAHUN 2010-2012 - , Sopian Sumantri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to determine factors that affect the success of mortgage execution auction in KPKNL Jakarta I. This research is important because the success rate is still low at 21 percent. The object in this auction is real property like land with or without building. Independent variables used in this study is the location in the form of real property within the central business district nearby, accessibility in the form of wide roads in front of real property, a land area of real property and the number of bidders who attend the auction. The data used in this study were obtained from the minutes of the mortgage execution auction held by Jakarta I KPKNL within three consecutive years from 2010 to 2012. Based on these data, about 5 percent were taken for samples or 78 auction minutes wether it sold or not. Samples were taken and processed by the method of logit regression models. The results showed that the factors that significantly influence the success of the mortgage execution auction in KPKNL Jakarta I were the location, accessibility, land area and number of bidders.